The stages in decision making process that influence customer purchase decision in buying house at Penang : A case study at Taman Pancur Utama Penang / Abd Latif Abd Raman...[et al.] - Abd Raman, Abd Latif; Abdul Mohsin, Abdul Amin; Mohd Noor, Mohd Faiz Ridwan (2013)
This research aims to know the process decision making in buying house at Taman Pancur Utama Penang. In there, are consist three type which had 300 units of house. The objective of this research is to know how the residential who buy the house at there make a process decision process, to identify the decision making process in buying house. A total respondent of 147 students from Taman Pancur Utama were selected to fill the sets of questionnaires that consists of 3 parts which are Demographic (Part A), Dependant Variable which is purchase decision (Part B). Independent Variable consist need recognition, search information, evaluate alternative and purchase decision (Part C-E) and the data were analyzed with Descriptive Statistics and Pearson Correlation of Statistical Package for Social Science (SPSS) version 20.0 software. The result indicates the process decision making buying house at Taman Pancur Utama.